Developing a methodology for characterising in-situ viscosity profiles in tumbling mills - Mangesana, Nobathembu (Department of Chemical Engineering, 2016)
Milling is the most expensive operation in a mineral processing circuit and accounts for the highest amount of energy utilized. The efficiency of the milling process is affected by the rate of breakage of bigger rocks and the rate of transport of the slurry within and out of the mill. The transport of material in the mill is dependent on the rheological properties of the slurry such as viscosity. Viscosity is therefore one of the important parameters that influences the transport of the material in the mill. Slurries in tumbling mills are known to exhibit non-Newtonian behaviour. This means slurry viscosity is not constant but is a function of shear rate. To characterize slurry transport in the mill it is necessary to study the viscosity distributions in order to determine regions of high and low resistance to flow in the mill. To determine the influence of slurry viscosity on the transport of particles it is important to quantify the typical shear rate ranges that occur inside the tumbling mill. The aim of this project w as to develop a methodology for characterising viscosity distributions inside a tumbling mill using in-situ shear rate distributions obtained from PEPT at different solids concentrations and mill speeds. The P EPT technique was used to study the in-situ mot ion of slurry particles with in tumbling mill charge using a single radioactive tracer. Rheology experiments were conducted using a U-tube rheometer. The rheometer experiments were performed to characterise the rheological behaviour of the El Soldado slurry at a wide range of shear rates. The PEPT results provided information about the typical shear rate ranges that occur inside the mill. The combination of these results enabled the quantification of viscosity distribution from the slope of the rheogram at typical shear rates found in the tumbling mill. The rheology results indicated that the Bingham model is the rheological model which gives the best description of the rheology of El Sol dado slurry. It had the highest R² adjusted values at all tested solids concentrations concentration ranges. The rheological behaviour of El Soldado slurry with a particle size fraction of -75+53 microns can be described as Newtonian. This means that the viscosity is constant and does not vary with shear rate. At low solids concentrations up to 30wt%, the viscosity values attained are equivalent to that of water at room temperature at 0.001 Pa.s. At higher solids concentrations up to 60wt%, the viscosity increases to 0.007 Pa.s for the shear rate range tested. The Bingham viscosity and yield stress increases in an exponential form with increasing solids concentration. PEPT experiments were conducted to quantify and characterise in-situ shear rates in a laboratory scale tumbling mill. The highest shear rates were obtained at the lowest solids concentration for both mill speeds. It was 30s-¹ at 60% critical mill speed and 36s-¹ at 75% critical mill speed. Mill shear rates decreased with increasing slurry solids concentration. This was attributed to increased particle-particle interactions and reduced voidage. There is less volume available for particle shearing. The magnitude of the maximum shear rate is higher for the 75% critical mill speed at all slurry solids concentrations compared to the shear rates at the lower mill speed. At a higher speed the mill charge is fairly dilated by the strong centrifugal effects that oppose the natural packing structure which results in an overall decrease in bulk density. The increased voidage allows more volume for relative motion, producing an overall increase in shear rate. The narrow shear rate range and the Bingham rheological behaviour of the slurry resulted in a constant viscosity value that could be used in a viscosity model provided the solids concentration is uniform across all regions of the mill. Viscosity is more significantly impacted by solids concentration than shear rate distributions in the tumbling mill. Work should be done to study the solids concentration profiles in the tumbling mill to provide better insight on areas of active transport.